Smart water metering: adoption, regulatory and social considerations. Issue 2 (3rd July 2021) - Koech, Richard; Cardell-Oliver, Rachel; Syme, Geoff
ABSTRACT: In recent decades, the adoption of smart water metering technology for water management has increased. The case for the adoption of smart water meters is mainly motivated by engineering and efficiency considerations around water conservation and related issues, for instance leak detection. At a consumer level, this can lead to improved feedback resulting in better customer control over consumption and household expenditure. The rate of adoption of smart water meters is dependent on many factors such as initial cost. The cost is expected to reduce as the technology matures and more options become available. The rate of adoption of the technology is also expected to be shaped by a variety of regulatory and social considerations. The purpose of this paper is to review the regulatory and social aspects that are likely to affect the adoption of the smart water metering technology in the future, with a focus on Australia. Instances of these aspects include privacy and health concerns, social acceptance, and communication strategies. It is expected that this paper will generate a healthy debate around the adoption of smart water meters to help the water sector to achieve a smooth transition from conventional to smart water meters.